Kajian Pengetahuan Dan Sikap Pekerja Terhadap Keselamatan Dan Kesehatan Kerja (Studi Kasus Pada Proyek Avian Tower Surabaya) - Mahendra, Rezha; Yakin, Kusnul; Bustamin, Maulidya Octaviani (Department of Civil Engineering, Dr. Soetomo University, 2019)
Along with the rapid pace of development of multi-storey building construction in indonesia, the role of eork accident risk control is felt to be increasingly important. Instead in reality, the application of the occupational safety and health management system (SMK3) is still often overlooked. This is indicated by the high number of work accidents. The purpose of this study was to determine the effect of K3 knowledge and worker attitudes on awareness of K3 behavior in the Avian Tower project partially or jointly. This study focuses on the finishing process of the construction of the Avian Tower project. The research method uses qualitative data collection techniques by distributing questionnaires to get responses about potensial hazards or the risk of workplace accidents. Data is processed usng the SPSS 21 computer appication program to obtain validity and reliability. The results of the research obtained from the validity test suggest that all variables are valid because the value of the relationship (r count) is greater tha the significance level (r table). For the reliability test of all variables, the alpha cronbach’s value is > 0.6, then it is declared reliable and based on the F test, the T test and coefficient o determination show if there is a significant influence between knowledge (X1), atttude (X2), K3 (Y). There is a positive effect of K3 knowledge on awareness of K3 behavior with evidence of t count > t table (3,765>2,032). there is positive influence on attitudes toward awareness of K3 behavior with evidence of t count > t table (2,134>2,032). there is a positive influence of knowledge and attitude towards awareness of K3 behavior with evidence of F count > F table (23,093>3,28).